Phase 3 Randomized Low-Dose Paclitaxel Chemoradiotherapy Study for Locally Advanced Non-Small Cell Lung Cancer - Lin, Hongmei; Chen, Yuhchyau; Shi, Anhui; Pandya, Kishan J.; Yu, Rong; Yuan, Yannan; Li, Jiancheng; Li, Hang; Wang, Yingjie; Xia, Tingyi; Feng, Linchun; Ma, Huimin; et al. (Frontiers in Oncology, 2016)
Introduction: Concurrent chemoradiotherapy (CCRT) is the standard treatment for locally advanced non-small cell lung cancer (LA-NSCLC), but is associated with poor chest tumor control. Here we report results of a randomized phase 3 study comparing two CCRT regimens in improving chest tumor control by low-dose paclitaxel chemoradiation for LA-NSCLC. Methods: Due to the logistics of local referral pattern, the study was designed to enroll patients with stage III LA-NSCLC who had completed 2-4 cycles of full-dose chemotherapy. One hundred thirty four were randomized to either Arm 1 (paclitaxel at 15 mg/m2, three times/wk [M, W, F] for 6 weeks, n=74), or Arm 2 (weekly paclitaxel at 45 mg/m2 for 6 weeks, n=60). Chest RT was 60-70 Gy in standard fractionation. Response rate was the primary endpoint, with recurrence-free survival (RFS) as the secondary endpoint. Results: From March 2006 to February 2013, seventy-one patients completed Arm 1 treatment, and 59 completed Arm 2 treatment. The response rate for Arm 1 was significantly higher (83.1%) than Arm 2 (54.2%) (p＝0.001). RFS was superior in Arm 1: median 14.6 months vs. 9.4 months, p=0.005, Hazard ratio (HR) 1.868 (95% CI 1.203, 2.901). Overall survival was not significantly different: median 32.6 months in Arm 1 vs. 31.3 months in Arm 2, p = 0.91, HR 0.969 (95% CI 0.552, 1.703). Toxicity was significantly lower in Arm 1 for grade 3 and 4 leucopenia/neutropenia (p<0.001). Conclusions: Pulsed low-dose paclitaxel CCRT resulted in significantly better RFS and tumor response rate, and less hematologic toxicities than weekly CCRT for LA-NSCLC.